(untitled) - Wilde, Oscar (Oxford, 1991)
When Dorian Gray sees the painting of his face, he falls in love with his own beauty. Nothing must touch his beauty, nothing must hurt or change it - not love, not even time. And so he cuts the link between his face and his heart, between his outside and his inside. His face does not change; it stays young and beauty. But the picture - painted with love - tells the true story. It shows the real Dorian Gray, who is growing old and ugly and full of hate.
Keywords: English fiction,English literature; 19th century